Design and Analysis of New Erbium Doped Fiber Amplifiers and Lasers - Bouzid, Belloui (2004)
Erbium doped fiber amplifiers and lasers have a great impact on optical communication due to their ideal advantages for the compensation of light energy during transmission through the fiber optic systems. This has been the focus of many research groups. Replacing the bottleneck electronic amplifier by the optical amplifier, a great improvement is made for the optical communication systems. New configurations have been conceived and realized in this thesis. They have shown a great enhancement in amplifier and laser performance parameters. Several new configurations, for example double pass with filter which also supports multiple wavelengths, have been demonstrated and investigated. The design and performance parameters of the new configurations are thoroughly characterized, showing an improvement in gain, noise figure output power flatness efficiency and side mode suppression ratio. Enhancement of results has been experimentally demonstrated, where a higher gain (56dB) and flat output power (<0.7dB), a higher signal to noise ratio (77dB) and a higher efficiency (22%) are demonstrated.